The Concept Of Islamic Economics In The School Of Baqir Al-Shadr: Introduction - Kartika; Rahman Ambo Mase; Muslimin H. Kara (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the Islamic economic thought of Baqir Al-Shadr, with a particular focus on the distinction between conventional economics and Islamic economics, as well as his concepts of ownership, wealth distribution, production, and consumption. Employing a qualitative approach through a structured literature review, the research examines Baqir Al-Shadr's seminal works, Iqtishaduna and Falsafatuna, alongside relevant secondary literature on Islamic economics. The findings reveal that Baqir Al-Shadr firmly differentiates Islamic economics from conventional economics by grounding it in moral, ethical, and social justice principles derived from Islamic teachings. He advocates for a balanced system where the state plays an active role in ensuring equitable wealth distribution and production that prioritizes public welfare. Furthermore, his views on ownership emphasize limited private rights and promote the management of resources for collective benefit. These insights contribute to the theoretical development of Islamic economics and highlight its potential as a viable alternative for establishing a more just and sustainable global economic order.